ҚУРАНЫ КӘРИЙМ ҲӘМ ҲӘДИСЛЕРДЕГИ ӘДЕП-ИКРАМЛЫЛЫҚ ТӘРБИЯ ҲАҚҚЫНДА - Абаев, С.; Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2020)
The article examines the role of religions heritage in the system of cultural heritage, especially the holy Qu’ran and hadith, which are the sacred sources of Islam, and explains the concepts of morality and ethics contained in them and their importance in the current educational process. In has also been conuincingly proved that this heritage is not only religious sources, but also univercal values, which are excellente educational tool that educates the perfect person.